Husn al-Zhann and Fear/Anxiety in Social Context among Muslim Emerging Adults - Damri, Rafi; Baitina, Syifaa Li (Al-Qalb : Jurnal Psikologi Islam, 2024)
As individuals enter adulthood, they may experience social pressures that lead to anxiety. If an individual experiences anxiety, it is likely to result in various negative impacts on their social life. In this case, it is important for individuals to instill more positive thinking through husn al-zhann (positive assumption). This study aims to identify the correlation between husn al-zhann and social anxiety among 122 emerging adults (n = 122). The results show that husn al-zhann is negatively correlated with social fear/anxiety. Aspects of husn al-zhann, such as the absence of hasad (envy) and feeling God's compassion, are also negatively correlated with social fear/anxiety. Looking at the aspects of social interaction and performance situations, social interaction situations were found to have a negative correlation with feeling God's compassion, the absence of hasad, and the attitude of husn al-zhann. Meanwhile, performance-related situations showed a negative correlation with feeling God's compassion and the absence of hasad. This study has limitations in terms of sample size. Therefore, future research is expected to investigate the relationship between these variables with a larger and more varied sample size, as well as a more complex relationship model.